Pemanfaatan Telegram Bot Untuk Pemenuhan Kebutuhan Informasi Sivitas Akademika UIN Imam Bonjol Padang Selama Pandemi Korona - Sa’adiyah, Halimahtus; Doni, Sefri; Syamsir, Syamsir (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2020)
The corona virus pandemic forced many fields to change work patterns including education. But many are not ready to face these changes. One institution that is not ready is the UIN Imam Bonjol Padang Library UPT where adequate access is not yet available to support academicians working and learning from home. Therefore, it is deemed necessary to develop a media that can cover these deficiencies, namely Telegram bot. Telegram was chosen because of the openness of the API which allows anyone to develop their own bot. This research uses a research development method which consists of five stages, namely requirements analysis, product design, product manufacture and testing. The results showed that the bot telegram was able to help the fulfillment of the information of the academics of UIN Imam Bonjol Padang in working and learning from home, thus the use of social messenger has a great opportunity to help libraries in serving users without having to be bound by time and space.